A rhodamine hydrazide–4-nitroindole-3-carboxaldehyde based turn on Hg2+ chemosensor: cytoplasmic live cell imaging, logic gate and memory device applications and computational studies. Issue 11 (3rd July 2018) - Bhowmick, Rahul; Musha Islam, Abu Saleh; Sasmal, Mihir; Katarkar, Atul; Ali, Mahammad
Abstract : A new, highly sensitive probeL 2 for the selective detection of Hg 2+ in organo-aqueous (H2 O:CH3 CN, 1:1, v/v, HEPES buffer, pH 7.2) medium has been synthesized from rhodamine 6G-hydrazide and 4-nitroindole-3-carboxaldehyde . It was thoroughly characterized by physicochemical techniques including single crystal X-ray diffraction studies. The reaction ofL 2 with Hg 2+ gives a 1:1 stoichiometry resulting in a 146 fold fluorescence enhancement and a binding constant ( K f ) of 3 × 10 4 M −1 . The spirolactam form of the probe is non-fluorescent; however, it shows dual channel (absorbance and fluorescence) recognition of Hg 2+ via CHEF effect through the opening of the spirolactam ring. The quantum yields ofL 2 (0.00045) andL 2 -Hg 2+ (0.29) show the higher stability of complex in the excited state over the free ligand. The 44.5 nM LOD value demonstrates the detection of Hg 2+ at a very low concentration range. Cell imaging studies show the cytoplasmic recognition of Hg 2+ byL 2 . Experimental results are comparable with theoretical values obtained by DFT studies. The fluorescence emission of the complex was completely quenched by I - and from the reversibility studies an advance level INHIBIT logic gate and memory device can be framed. Graphical Abstract: